Pengaruh Islamic Human Capital dan Pengembangan Karir terhadap Kinerja Karyawan Bank Syariah - Rahayu Ningsih; Asyari Asyari; Iiz Izmuddin (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2020)
This study aims to measure the effect of Islamic Human Capital and career development on the performance of Islamic Bank employees in Pasaman district. This research was a causality research with a quantitative approach based on statistical data and empirical data at the research location. The population in this study were employees of Islamic Banks in Pasaman district. Sampling was carried out by total sampling, consisting of Bank Syariah Mandiri, Bank Syariah BTPN and Bank Nagari Syariah, as many as 32 people. Data were collected using questionnaires, observation and documentation. Based on the results of the data analysis, it appears that Islamic Human Capital has a positive effect on employee performance (p-value = 0.000). While the career development variable does not have a positive and significant effect on employee performance (p-value = 0.589). Simultaneously, the Islamic Human Capital variable and career development have an effect on employee performance (p-value = 0.000). The findings of this study reveal the importance of improving Islamic Human Capital and career development efforts in improving the performance of Islamic Bank employees, especially in Pasaman districtPenelitian ini bertujuan untuk mengukur pengaruh Islamic Human Capital dan pengembangan karirterhadap kinerja karyawan Bank Syariah di Kabupaten Pasaman. Penelitian ini merupakan penelitian kausalitas dengan pendekatan kuantitatif berdasarkan data statistik dan data empiris di lokasi penelitian. Populasi dalam penelitian ini adalah karyawan dari Bank Syariah yang terdapat di Kabupaten Pasaman. Penarikan sampel dilakukan dengan total sampling, yang terdiri dari Bank Syariah Mandiri, Bank Syariah BTPN dan Bank Nagari Syariah, sebanyak 32 orang. Teknik pengumpulan data adalah dengan metode kuesioner, observasi dan dokumentasi, Berdasarkan hasil analisis data terlihat bahwa Islamic Human Capital berpengaruh positif terhadap kinerja karyawan (p-value = 0,000). Sedangkan variabel pengembangan karir tidak berpengaruh positif dan signifikan terhadap kinerja karyawan (p-value = 0,589). Secara simultan, variabel Islamic Human Capital dan pengembangan karir berpengaruh terhadap kinerja karyawan (p-value = 0.000). Temuan penelitian ini mengungkap pentingnya perbaikan Islamic Human Capital dan dan upaya pengembangan karir dalam meningkatkan kinerja karyawan Bank Syariah, terutama di kabupaten Pasaman